Breaking the Cycle of Adversity in Vulnerable Children and Families: A Thirty-Five Year Study of At-Risk Lower Income Families - Stack, Dale M.; Serbin, Lisa A.; Mantis, Irene; Kingdon, Danielle (International Journal for Family Research and Policy, 2015)
Family poverty and childhood adversity follow an intergenerational cycle. Children raised under conditions of social and economic disadvantage are likely to raise their own children under similar conditions. To break this cycle, we need to understand why it occurs and why children’s health and development are threatened by disadvantaged conditions of child rearing. We also need to identify protective processes, such as a healthy and supportive parent-child relationship, that may lead to positive health and development under conditions of risk. The longitudinal findings presented in this paper are a summary drawn from the published results of the Concordia Longitudinal Risk Project: an ongoing, three generational, 35-year study of Montréal families from lower income neighborhoods. The original sample comprised over 4,000 school-aged children. Many of these participants are now parents, and their children have been recruited into the study. Among the long-term processes we examine are family violence, fathers’ presence versus absence in the home, and impact of parental mental health problems on children’s health and development. Drawing from an in-depth assessment of parent-child interactions from infancy to preadolescence, we show how family interaction patterns over time can help to achieve positive outcomes for children. Based on statistical modeling techniques and hierarchical regression, we illustrate the ways in which family poverty and adversity during the childhood of one generation lead to conditions of risk for poverty and adversity in the next, via stressful rearing conditions, family violence, mental and physical health problems, and long-term behavioural problems. From the opposite perspective, we identify the environmental, social, educational and behavioural factors that predict positive outcomes for many children, despite disadvantaged conditions. We also highlight the vital role that parents play in this process and how negative intergenerational patterns may be broken by positive parenting, cognitive stimulation, and environmental support across childhood.